Corruption in Higher Education; A Comparative Studies on Whistleblowing System between University of Stanford and Universitas Indonesia - Saomi Rizqiyanto; Muhammad Chaerul Anwar; Rezky Ramadhan Antuli (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
This study seeks to demonstrate the utilisation of the whistleblower system in higher education to mitigate academic dishonesty and fraud, emphasising a comparison between Stanford University in the United States and the University of Indonesia. The study's findings indicate that both universities acknowledge the significance of witness protection within the whistleblowing framework, particularly to safeguard the safety and security of whistleblowers. Stanford University and the University of Indonesia provide conventional reporting mechanisms; nevertheless, Stanford University possesses superior reporting governance and regulations. Both schools offer application-based reporting mechanisms; however, Stanford University maintains an exceptional framework for reporting management rules and whistleblower protection. This study's conclusions aim to assist Indonesian universities in establishing efficient reporting methods and procedures to eliminate corruption and enhance academic integrity. This study employs a qualitative research methodology encompassing two primary approaches: a literary approach and a law approach. The literature review method examines academic literature, publications, and regulations about whistleblowing in higher education institutions in the United States and Indonesia. This literature analysis examines the optimal practices of whistleblower systems in several international universities and their implications for higher education in Indonesia. A legal framework is utilised to explore the existing regulations and statutes, specifically concerning witness protection, whistleblower security, and the enforcement of academic integrity. This entails an examination of the legislation and internal university policies concerning whistleblowing in each nation. The study offers a comprehensive comparative analysis of the effective implementation of whistleblower systems in Indonesian universities, along with recommendations for enhancing reporting governance policies to foster a more transparent and accountable academic environment.